The Effect of Toothbrush Innovation: Fun Play, Beautiful Teeth along with Parent Participation on the Brushing behavior of Preschool Children - ยางธิสาร อิทธิพัทธิ์; อภัยโส นฤเบศร์; หนันลี พัชรินทร์; แก้วฝ่าย จารุวิชญ์; แสนทวีสุข วีรภัทร; ทองแพ จิราภรณ์; ใจสว่าง ระพีพรรณ; บุญโท ปณิตา; โคตรศรีเมือง สุดารัตน์; ลีสีสุข ขวัญฤดี; ชินชาด สุดารัตน์; ภูนากลม เนตรฤทัย (Journal of Health Science of Thailand, 2024)
This quasi-experimental study aimed to study the effect of toothbrush innovation: Fun Play, Beautiful Teeth along with parent participation on the brushing behavior of preschool children. Forty male and female preschool children aged 3-4 years old at a child development center in one province were recruited by purposive sampling, divided into experimental and control groups with 20 children in each group. The experimental group received the toothbrush innovation: Fun Play, Beautiful Teeth along with parent participation whereas the control group was taught the correct way to brush their teeth. Personal data of the samples were analyzed by using descriptive statistics, Paired t-test was conducted to compare the mean score of brushing behavior before and after the experiment of the experimental group, and an independent t-test was conducted to compare the mean score of brushing behavior between the experimental and control group. The results showed that the experimental group had the mean score of brushing behavior significantly higher than before the experiment (p<0.05) and the experimental group had the mean score of brushing behavior significantly higher than the control group (p<0.05). In conclusion, the results of the study showed that the toothbrush innovation: Fun Play, Beautiful Teeth along with parent participation, was effective in promoting brushing behavior and preventing oral and dental health problems, ultimately resulting in preschool children having appropriate growth and development.